Comparison of the Economic Development of Five European Microstates in the Last 20 Years - Loudín, Tomáš; Kopřiva, Bohumil; Vysoká škola ekonomická v Praze. Fakulta managementu (2008)
This bachelor thesis reports the basic information about the five European microstates (Andorra, Liechtenstein, Malta, Monaco, and San Marino). In the first part the thesis describes geographical, demographical and historical review and political and economical conditions. In the second part the thesis compares the development of their economies in the last 25 years by the help of several indexes and indicators. The last part summarizes strong and weak points of the individual country and concerns in the relationships with the rest of Europe
Vedoucí práce: Bohumil Kopřiva
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze, Fakulta managementu, 2008
Obsahuje bibliografii
Rok obhajoby 2008
Keywords: hospodářské poměry; Andorra; Lichtenštejnsko; Malta; Monako; San Marino; management [obor bakal. práce]; bakalářské práce; economic conditions; Andorra; Liechtenstein; Malta; Monaco; San Marino; bachelor's theses